Muscle stretching induces twitch contractions without activation of stretch-activated channels in intact rat trabeculae. (14th October 2021) - Satoh, W; Sato, H; Kumasaka, K; Shindoh, C; Miura, M
Abstract: Introduction: Mechano-electric coupling (MEC) means that muscle stretching can induce action potentials. Stretch-activated channels (SACs) have been believed to play important roles in their induction. Purpose: To investigate what degree of muscle stretching can induce MEC-mediated action potentials and what roles SACs play in their induction. Methods: Trabeculae were obtained from right ventricles of rat hearts. Force was measured with a strain gauge, sarcomere length (SL) with a laser diffraction technique, and [Ca2+]i with fura-2 (24°C). The SL was set at 2.0 μm at the resting condition. Trabeculae were stimulated electrically at 400-ms intervals for 7.5 s. Various degrees of muscle stretching were applied at 500 ms after the last stimulus of the electrical train to determine the minimal SL (SL-AP) at which an action potential or a twitch contraction was induced by the stretching (0.7 mM [Ca2+]o). Results: The SL-AP was 2.34±0.02 μm (n=8) when trabeculae were stretched rapidly from a SL of 2.0 μm (400-ms stimulation intervals, 0.7 mM [Ca2+]o). The SL-AP was not changed by increasing the stimulation intervals from 400 to 2000 ms (n=7), by increasing [Ca2+]o from 0.7 to 2 mM (n=8), and by adding 1 μM isoproterenol (n=8), suggesting that Ca2+ loading within the myocardium has no effect on the SL-AP. Surprisingly, the SL-AP was not changed by adding 5 μM GsMTx4 (n=8), 10 mM Gd3+ (n=9), 100 μM (n=8) and 200 μM streptomycin (n=11), revealing that SACs play no roles in the determination of SL-AP. The SL-AP was not changed by adding 1 μM ryanodine (n=5) and 30 μM cyclopiazonic acid and was not changed by adding 3 μM diphenyleneiodonium chloride (n=8) and 10 μM colchicine, suggesting that Ca2+ leak from the SR and activation of NADPH oxidase has no effect on the SL-AP. In contrast, elevation of temperature from 23 to 36°C decreased the SL-AP from 2.35±0.01 to 2.34±0.02 μm (p<0.05, n=7). Elevation of extracellular K+ ([K+]o) from 5 to 10 mM increased the SL-AP from 2.35±0.01 to 2.38±0.01 μm (p<0.01, n=7), while reduction of [K+]o to 5 mM decreased it to 2.36±0.01 μm (p<0.05, n=7), suggesting that depolarization of membrane potential suppresses MEC-mediated twitch contractions. The SL-AP was increased from 2.34±0.01 to 2.36±0.01 μm (p<0.01, n=7) when stretching was applied at a shorter interval after the last stimulus, i.e., 200 ms. After electrical stimulation at 300-ms stimulation intervals for 30 s, arrhythmias were induced by a MEC-mediated twitch contraction in 6 out of 9 trabeculae when stretching was applied at 500 ms after the last stimulus, while they were induced only in 2 out of 9 trabeculae without the stretching (4 mM [Ca2+]o, 1 μM isoproterenol). Conclusions: These results suggest that muscle stretching causes membrane excitation, which potentially induces arrhythmias and that activation of SACs, Ca2+ release from the SR, and activation of NADPH oxidase by muscle stretching are not involved in the excitation. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Grant-in-Aid for Scientific Research (C) from Japan Society for the Promotion of Science.